Structural change of Cu/ZnO by reduction of ZnO in Cu/ZnO with methanol - Jung, KD; Joo, OS; Han, SH (SPRINGER, 2000)
The reducibility of ZnO was investigated in the temperature range of 523-623 K in a stream of a reducing agent such as H-2, CO, and methanol. ZnO was reduced only in the presence of copper in the vicinity of ZnO with CO and methanol, but it was not reduced with H-2. Methanol was a stronger reducing agent in the reduction of ZnO than CO, while CO was stronger in the reduction of CuO than methanol. Two types of brass were observed resulting from the reduction of ZnO in the Cu/ZnO sample by XRD. Zanghengite brass started to be formed at 573 K in addition to alpha-brass which was observed at the temperature above 523 K in the temperature range of 523-623 K during the ZnO reduction with methanol. The carbon monoxide chemisorption showed that the copper surface areas decreased during the reduction of ZnO with methanol.
Keywords: ALPHA-BRASS FORMATION; ZINC OXIDE CATALYSTS; COPPER; CU/SIO2